AMINOGLYCOSIDE RESISTANCE GENES IN Pseudomonas aeruginosa ISOLATES FROM CUMANA, VENEZUELA - TEIXEIRA, Bertinellys; RODULFO, Hectorina; CARREÑO, Numirin; GUZMÁN, Militza; SALAZAR, Elsa; DONATO, Marcos DE (Revista do Instituto de Medicina Tropical de São Paulo, 2016)
The enzymatic modification of aminoglycosides by aminoglycoside-acetyltransferases (AAC), aminoglycoside-adenyltransferases (AAD), and aminoglycoside-phosphotransferases (APH), is the most common resistance mechanism in P. aeruginosa and these enzymes can be coded on mobile genetic elements that contribute to their dispersion. One hundred and thirty seven P. aeruginosa isolates from the University Hospital, Cumana, Venezuela (HUAPA) were evaluated. Antimicrobial susceptibility was determined by the disk diffusion method and theaac, aadB and aph genes were detected by PCR. Most of the P. aeruginosa isolates (33/137) were identified from the Intensive Care Unit (ICU), mainly from discharges (96/137). The frequency of resistant P. aeruginosaisolates was found to be higher for the aminoglycosides tobramycin and amikacin (30.7 and 29.9%, respectively). Phenotype VI, resistant to these antibiotics, was the most frequent (14/49), followed by phenotype I, resistant to all the aminoglycosides tested (12/49). The aac(6´)-Ib,aphA1 and aadB genes were the most frequently detected, and the simultaneous presence of several resistance genes in the same isolate was demonstrated. Aminoglycoside resistance in isolates ofP. aeruginosa at the HUAPA is partly due to the presence of the aac(6´)-Ib, aphA1 andaadB genes, but the high rates of antimicrobial resistance suggest the existence of several mechanisms acting together. This is the first report of aminoglycoside resistance genes in Venezuela and one of the few in Latin America.